Glycosylation with ulosonates under Mitsunobu conditions: scope and limitations. (14th August 2020) - Kánya, Nándor; Kun, Sándor; Batta, Gyula; Somsák, László
Abstract : Mitsunobu reactions on highly hindered tertiary type hydroxy groups of ulosonates: from 47 NuH compounds O-, N-, and S-nucleophiles gave the corresponding ulosidonates in 30–78% yields, while C-nucleophiles were unreactive. Abstract : A systematic study was performed by using Mitsunobu conditions (diethyl azodicarboxylate, Ph3 P or n -Bu3 P in THF or CH3 CN) for glycosylations with methyl 3, 4, 5, 7-tetra- O -benzoyl-α-d - gluco -hept-2-ulopyranosonate. From a set of 47 O-, N-, S- and C-nucleophiles, phenols and N -hydroxy compounds with a p K a of 5–8, phthalimide, benzotriazole, 6-chloropurine, an oxazolidinedione and several tetrazoles with a p K a of 4–8, and thiophenol gave the corresponding products in moderate to very good yields, while C-nucleophiles were unreactive. Trihaloacetanilides underwent O -glycosylation to give O -glycosyl- N -aryl trihaloacetimidates which could not be made by conventional O -imidoylations. All reactions were highly stereoselective to produce the β(d ) anomers only. With methyl (5-acetamido-4, 7, 8, 9-tetra- O -acetyl-3, 5-dideoxy-d - glycero -d - galacto -2-nonulopyranose)onate phenols and benzotriazole resulted in the expected products, but all other nucleophiles failed to react. While these transformations gave anomeric mixtures in a ratio close to 1 : 1 at room temperature, the α-selectivity increased to 92 : 8 at −30 °C. An o -nitrophenyl sialoside was converted to a spiro-benzoxazinone derivative by reduction of the nitro group and subsequent spontaneous ring closure.